Estimation of the Fundamental Frequency of the Speech Signal Compressed by MP3 Algorithm - Zoran MILIVOJEVIC; Darko BRODIC (Archives of Acoustics)
The paper analyzes the estimation of the fundamental frequency from the real speech signal which is obtained by recording the speaker in the real acoustic environment modeled by the MP3 method. The estimation was performed by the Picking-Peaks algorithm with implemented parametric cubic convolution (PCC) interpolation. The efficiency of PCC was tested for Catmull-Rom, Greville, and Greville two- parametric kernel. Depending on MSE, a window that gives optimal results was chosen.